Correlation of Regulatory T Cells Percentage and Lung Tuberculosis in Children - Melinda; Ery Olivianto; HMS Chandra Kusuma (Pediatric Sciences Journal, 2022)
Introduction: The prevalence of TB in Indonesia reaches 1.59 new cases per 1000 population and 27.3% are pediatric patients. Currently in Indonesia, the incidence of TB in children is still high, even though the Bacille Calmette Guerin (BCG) vaccination has been a mandatory immunization program since 1977. The role of T-Regulatory Cell (Treg) in the Mtb infection is very complicated. Method: This observational study using cross sectional analyzed quantity of Treg Cells in the circulation of pediatric TB and non-TB patients. Measurement of circulatory Treg cell percentage was performed using Flow Cytometry. Result: We found that pediatric TB patients have significantly higher that were almost two-fold higher Treg cell percentage compared to non-TB patients (3.51% vs. 1.86%; p < 0.001). It is concluded that there is an increase in the percentage of Treg cells in children with pulmonary TB compared to children who didn’t had TB infection. Conclusion:This finding provides an understanding of the complex mechanism of Treg cells in children with pulmonary tuberculosis, so that it can become the basis for the development of management of pediatric pulmonary TB and reduce morbidity and mortality of children due to pulmonary TB.